The effect of cooperative learning strategy on the social and sport skills of middle school students in Baghdad, Iraq - Mohseen, Hayder S. (2012)
In recent years, several observers have already drawn attention to the problems faced by the Iraqi children, who have been facing challenges in the classroom on a daily basis and are suffering from different forms of social skill vulnerability. Therefore, the use all possible scientific and practical means is necessary to mitigate these common recurring problems, and to aid the learner in fulfilling the aims of physical education classes. The UNICEF, in cooperation with the Iraqi MOE, promoted educational programmes that provide essential support services to improve children’s morale and to provide them with psychosocial care, especially through physical and recreational activities in schools The current study aimed to use a format of Cooperative Learning Strategy (CLS), which involved group work where groups were involved in structured tasks with identifiable outcomes called Student Team’s Achievement Division (STAD) as a basis for the intervention in order to promote the Iraqi middle school students' social and sport (i.e.volleyball) skills. However, an intervention programme was part of a new learning style, combining the sport and social skills in which students (ages = 12.8 years, N =60) were invited to participate in physical education lessons. Both the experimental and control groups took a pre-test before the treatment phase of the study (week one). The first post-test was administered to students in both groups on week 8 and a second post-test was given to the participants on the week 12 of treatment period. Iraqi Social Skills Rating Questionnaire (ISSRQ) was used to measure the social skills. In addition, the American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD) test was used to measure the sport skills in terms of volleying, serving, passing, and set-up skills. Statistical analysis included (group× time) repeated measures ANOVA and MANOVA to determine between and within group mean differences in order to ascertain whether there were significant differences among the pre-test, post-tests one, and two scores and within the two groups. This study showed that social and sport (volleyball) skills gains were made by students in the CLS and the teacher-centered method groups. The students in the CLS group reflected a higher rate of improvement regarding the total social skills and overall sport skills throughout 12 weeks compared with the control group. This study manifests that the cooperative learning approach holds many promises for physical education and sport activities. Nevertheless, it would be a great challenge if it were adopted throughout Iraqi schools, especially in the physical education and sport activities.